FINANCIAL ACCOUNTING LITERACY AND PERSONAL FINANCIAL MANAGEMENT BEHAVIOR AMONG GENERATION Z: THE MODERATING ROLE OF SOCIAL MEDIA - Budi Safatul Anam; Masyitah (Gabungan Riset Edukasi dan Ekplorasi Teori (GREET), 2026)
The ease of accessing financial information through social media has transformed how Generation Z acquires knowledge and shapes their financial behavior, yet this does not necessarily translate into sound personal financial management. This study aims to analyze the effect of financial accounting literacy on the personal financial management behavior of Generation Z, and to test and explore the role of social media as a source of financial information in moderating this relationship. This study employs an explanatory sequential mixed methods design, beginning with a quantitative phase using a survey of 150 purposively selected Generation Z respondents (born 1997-2012), analyzed using Moderated Regression Analysis (MRA), followed by a qualitative phase through in-depth interviews with eight selected informants to deepen and explain the quantitative findings. The (illustrative) quantitative results indicate that financial accounting literacy has a significant positive effect on personal financial management behavior, social media as a source of financial information also has a significant positive effect, and, more interestingly, social media significantly and positively moderates (strengthens) the effect of financial literacy on financial management behavior. The qualitative phase reveals the mechanism behind these findings: social media functions as a 'double-edged sword' for Generation Z. For individuals with adequate financial literacy, social media reinforces understanding through the ability to filter and evaluate content credibility (critical financial literacy), whereas for individuals with low literacy, exposure to finfluencer content risks encouraging impulsive and speculative financial behavior driven by information overload and fear of missing out (FOMO) toward investment trends. This study contributes theoretically by broadening the understanding of the dual role of social media in digital financial literacy, and offers practical implications for educational institutions and regulators in designing financial education programs that equip Generation Z with critical thinking skills toward financial content on social media, rather than mere access to information.